NAVIGATING SEVERE AORTIC INSUFFICIENCY WHEN SURGERY IS NOT AN OPTION - Thu Tran, MD (Elsevier, 2024)
Therapeutic Area: Heart Failure Case Presentation: 47-year-old male with congenital bicuspid aortic valve and known dilated aortic root measuring 4.4cm presented with 2 weeks of progressive exertional dyspnea, orthopnea and lower extremity edema. History was also notable for recent relapse of polysubstance use disorder (methamphetamine and fentanyl), and AIDS with recent self-discontinuation of antiretrovirals. Initial workup was significant for newly diagnosed heart failure with reduced ejection fraction of 40%, 4+ aortic regurgitation and a saccular ascending aortic aneurysm measuring 7.5 x 6.4cm in cross-sectional diameter and 8.2cm in length. Plan was to medically optimize current heart failure exacerbation and demonstration of medication adherence prior to consideration of valve repair. Unfortunately, patient acutely decompensated on day 2 of hospital stay with severe hypotension, unequal blood pressures and elevated lactate concerning for acute aortic dissection. He was stabilized in the ICU, intubated and on pressor support. He underwent emergent chest imaging that ruled out acute dissection but demonstrated findings concerning for pneumonia. He was treated for septic shock with prolonged extensive antibiotic course due to his immunocompromised state. Given his comorbidities and acute instability, he was deemed not a suitable surgical candidate. His medical management then focused around afterload reduction with vasodilators such as sodium nitroprusside to augment forward flow and favoring mild tachycardia to maintain cardiac output. His hospital course was further challenged by hyperactive delirium and difficulty down titrating sedation with episodes of severe hypertension leading to flash pulmonary edema. Despite effort from the multidisciplinary team to care for the patient, his medical management continued to be futile and patient was ultimately transitioned to comfort care. Background: In patients with chronic severe aortic insufficiency, surgical interventions are often the definitive and lifesaving treatment. However, when surgery is not an option, medical management is limited with temporizing measures. Current guidelines recommend use of vasodilators to improve forward flow and inotropes to maintain cardiac output. Conclusions: This case speaks to the challenges of medical optimization in socially complex patients with severe aortic insufficiency complicated by debilitating comorbidities and highlights the importance of early engagement from multidisciplinary team and prompt goals of care discussions.